Singapore's Economic Growth Dynamics - Putri, Erlisse Kurnia; Setyowati, Eni (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: this study employs an Error-Correction Model to examine how foreign direct investment (FDI), renewable energy consumption, labor, and inflation are associated with economic growth in SingaporeMethodology: Using annual Singapore data for 2000 to 2024, this study employs an Error-Correction Model to capture both short-run dynamics and long-run equilibrium relationships between FDI, renewable energy consumption, labor, inflation, and economic growth.Results: The short-run estimates indicate that growth is responsive to FDI, renewable energy use, and inflation, whereas labor does not exhibit a statistically significant effect. In contrast, the long-run results reveal that renewable energy, labor, and inflation exert significant influences on growth, while FDI becomes non-significant. The specification accounts for 71.61% of the variation in economic growth.Applications/Originality/Value: These findings point to the presence of frictions in the clean-energy transition and rigidities in the labor market, as well as an asymmetric contribution of FDI relative to renewables across time horizons. From a policy perspective, the implications include the importance of maintaining macroeconomic stability, accelerating the rollout of renewable energy, alleviating constraints in the labor market, and directing investment toward projects that enhance productivity.